The Impact of Digital Literacy on English Language Learning: A Study on Students’ Perspectives - Farhan, Farhan; Dollah, Syarifuddin; Radhiyani, Fitri (Journal of Excellence in English Language Education, 2025)
This research using qualitative methods aims to find out students' perspective of impact in use of digital literacy in the classroom. The subject of this research was five students of SMPN 4 Sungguminasa. They were chosen using a checklist of observations. The primary method of data collection was the interview. The study's findings demonstrated that students' opinions regarding the use of digital literacy in the classroom are generally positive. Most of them think that the uses of technology in the classroom are convenience, interactive, and fun. This is aligned with the two principles of Technology acceptance models (TAM), perceive of use (PU) and perceive ease of use (PEOU). They found the use of technology make them easier to understand the lesson that given by the teacher. The only challenge they faced in the use of technology in the classroom is network problem. In conclusion the students show the acceptance of the application of technology in education.